Shades of gray - Reeder, Carolyn (New York, NY : Aladdin Paperbacks, 1999)
At the end of the Civil War, twelve-year-old Will, having lost all his immediate family, reluctantly leaves his city home to live in the Virginia countryside with his aunt and the uncle he considers a "traitor" because he refused to take part in the war.
"Winner of the Scott O'Dell Award"--Cover.
"Aladdin historical fiction"--Cover.
Keywords: Orphans -- Fiction; Uncles -- Fiction; Conscientious objectors -- Fiction; United States -- History -- Civil War, 1861-1865 -- Fiction; Virginia -- Fiction